Functional neutralization of HIV-1 Vif protein by intracellular immunization inhibits reverse transcription and viral replication - Goncalves, J (2015)
Human immunodeficiency virus type 1 (HIV-1)-encoded Vif protein is important for viral replication and infectivity. Vif is a cytoplasmic protein that acts during virus assembly by an unknown mechanism, enhancing viral infectivity. The action of Vif in producer cells is essential for the completion of proviral DNA synthesis following virus entry. Therefore, Vif is considered to be an important alternative therapeutic target for inhibition of viral infectivity at the level of viral assembly and reverse transcription. To gain insight into this process, we developed a Vif-specific single-chain antibody and expressed it intracellularly in the cytoplasm. This intrabody efficiently bound Vif protein and neutralized its infectivity-enhancing function. Intrabody-expressing cells were shown to be highly refractory to challenge with different strains of HIV-1 and HIV-1-infected cells. Inhibition of Vif by intrabody expression in the donor cell produced viral particles that do not complete reverse transcription in the recipient cell. The anti-Vif scFv was shown to be specific for Vif protein because its function was observed only in nonpermissive cells (H9, CEM, and U38). Moreover, transduction of peripheral blood mononuclear cells with an HIV-derived retroviral vector expressing Vif intrabody was shown to confer resistance to laboratory-adapted and primary HIV strains. This study provides biochemical evidence for the role of Vif in the HrV-1 lifecycle and validates Vif as a target for the control of HIV-1 infection.